Strategy of crisis management of the pharmaceutical industry in the Republic of Sakha (Yakutiya) - E. R. Romanova; V. S. Stel’makh (Вестник университета, 2019)
Over the past fifteen years, the pharmaceutical industry is actively developing both in Russia and abroad. At the same time, the economic condition of pharmaceutical enterprises in the regions is heterogeneous. A practical continuation of the author’s research in the field of anti-crisis monitoring of industrial enterprises has been presented in the article: testing of the previously proposed methodological provisions, aimed at the development of the pharmaceutical industry on the example of a particular region. The indicators of the activity of pharmaceutical enterprises in the context of federal districts have been considered, the features of the pharmaceutical industry of the Far Eastern region have been indicated. On the basis of anti-crisis monitoring of indicators on the author’s bankruptcy assessment model, the possibility of creating a pharmaceutical cluster in the Sakha Republic (Yakutia) for the sustainable development of the enterprise and industry in the region has been considered.